Sams teach yourself Facebook for business in 10 minutes - Smith, Bud E. (Sams teach yourself., 2011)
Contains a series of ten-minute lessons on the business uses of Facebook, explaining how to set up a personal Facebook profile, find and install applications, create a fan page for a business, claim a Facebook Places page, combine business and Places pages, edit Places pages, support multiple locations, drive traffic to a Places page, create Facebook Deals and Facebook Ads, budget for Facebook Ads, and track the impact of a Facebook presence.